Radiation-induced thumbs carcinoma due to practicing dental X-ray - Esam S Halboub; Imad Barngkgei; Osama Alsabbagh; Omar Hamadah (Wolters Kluwer Medknow Publications, 2015)
Dealing with diagnostic X-ray radiation may result in serious health problems, unless protection guidelines are followed. This became prevalent immediately a decade following the invention of X-ray radiation, where it had not been known that the accumulative exposure to X-ray radiation may carry huge health hazards. The reoccurrence of various fatal cancer cases compelled the concerned health authorities to develop safety standards to be followed by all X-ray clinics and technicians worldwide. This report documents the clinical case of a dental radiographer, who developed thumbs carcinoma after 15 years of practicing the profession, most likely due to his neglect of the X-ray radiation protection guidelines.